Statistical analysis for strength properties of polypropylene-fibre-reinforced fly ash concrete - Karahan, O.; Tanyildizi, H.; Atis, C. D. (Thomas Telford Publishing, 2009)
In this study, the strength properties of polypropylene (PP)-fibre-reinforced fly-ash concrete were investigated experimentally and statistically. Three control factors (amount of fly ash, amount of PP fibre and curing time) were used for this study. The fly ash content that was used was 0, 60 and 120 kg/m(3) and the fibre content was 0, 0.45. 0.90 and 1.80 kg/m(3). The specimens were cured in standard curing conditions at temperature 23 +/- 2 degrees C for periods of 7, 28, 90 and 365 days. At the end of the curing period, the average of three specimens was tested to measure each of the concrete strength properties (compressive strength, flexural tensile strength and splitting tensile strength). Furthermore, the level of importance of these parameters on the strength properties was determined by rising the analysis of variance (Anova) method.
Keywords: Silica Fume; Mechanical-Properties; Performance; Wedm